TINJAUAN PENANGANAN LIMBAH MEDIS PADAT DI UNIT DONOR DARAH PMI CABANG KOTA BANDUNG TAHUN 2017 - Akmal Firmansyah Putra (Poltekkes Kemenkes Bandung, 2017)
The Overview Of Handling Medical Solid Waste In PMI Blood Donor Unit Bandung City Branch 2017. Medical waste is needed a special handling because of its existence is very infectious/infect so it will be dangerous and can transmit the disease. Separation of medical and non medical waste should be done to avoid the dispersion of disease and also avoid accident transmission for officers, donors and around the Blood Donor Unit areas. The purpose of this study is to know the description of the handling of solid medical waste at PMI Blood Donor Unit Bandung starting from the storage / sorting stage, the collection stage, the transportation stage, and the temporary disposal or temporary stage, and the level of knowledge and aspects of employee attitude in handling Solid medical waste. This research is descriptive with survey and observation method in general terms. The results obtained that the handling of solid medical waste in PMI (Red Cross Of Indonesia) Blood Donor Unit Bandung City Branch, there are several items that didn’t meet the requirements as in the phase of sorting medical waste using yellow plastic but not possess the biohazard, and not only at the stage of waste bins after discharge isn’t immediately disinfected directly, but also at the transporting stage of the conveyance after used it, it’s not disinfected directly. The phase of collection, temporary storage, and temporary storage stages are categorized as a eligible. Aspects of knowledge and attitudes on paramedics and janitors are good. Based on the results of the study, the authors propose proposition to make the manager or management as a subject in this research to see the aspects of facilitation both facilities and infrastructure and providing training to employees.